Types of assessment and their importance in teaching process (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the study of types of assessment and their importance in teaching process. Assessment is the process of documenting in measurable terms, knowledge, skills, attitudes and beliefs. The term assessment is generally used to refer to all activities of the learners. Moreover this article deals with the results of pre and post-testing results of language learning classes. Well-designed assessment has numerous benefits aside from the obvious one of providing a measure of students' progress as it can be a means to engage students with their learning. Ideally then, you should aim to support active learning rather than assessment of learning to ensure that the assessment process is an integral part of students' education.